Quarry resource planning for the states of Selangor, Terengganu, Kelantan, Sabah and Sarawak: a general overview & the statistical modelling for demand of aggregates / Zulkifli Ab Ghani Hilmi … [et al.] - Ab Ghani Hilmi, Zulkifli; Sahat, Sa'diah; Mohamad, Hajar; Abdul Rashid, Saharani (2004)
Quarrying is an important economic activity since infrastructure and industrial development led to a continuing demand for rock aggregates in the country. Under the Eighth Malaysian Plan (2001-2005), the construction sector is expected to grow at an annual rate o 6.7%. However, the government and the society are increasingly sensitive on safety and environmental issues related to exploitation of rock materials. The government, through the Department of Minerals and Geoscience Malaysia, commissioned a mining consultant firm to conduct studies and prepare reports on quarry resource planning for every state in the country. The primary objective of the project is to identify policies and strategies for the sustainable development of the quarrying industry in view of the economic interest, social and safety considerations, impact on environment and conservation of natural resources.